The Influence of the Principal's Leadership Style on the Quality of Education at SMP Swasta Masehi Berastagi for the 2023/2024 Academic Year - Sitopu, Juliaman; Dalimunthe, Elvi Febrianti; Budiarta, Kustoro; Dalimunthe, Muhammad Bukhori (ProBisnis : Jurnal Manajemen, 2024)
This study discusses the leadership style of school principals in SMP Negeri 1 Berastagi and its impact on the quality of education. The purpose of this article is to understand the leadership style of school principals and how it affects the quality of education in SMP Negeri 1 Berastagi. The type of research in this article refers to ex-post facto involving all ASN and non-ASN teachers at SMP Negeri 1 Berastagi, which numbers to 53 people, regardless of whether they are ASN or honorarium teachers. The sample size was 53, and the data was collected using questionnaires and documentation. The study was analyzed using statistical inference. The descriptive results of the study are the leadership style of school principals in SMP Negeri 1 Berastagi, with a score of 77.8, a minimum score of 56, a maximum score of 92, a standard deviation of 8.6, and a variance of 75. It is categorized as having a frequency of 29 people, which is 55%. The quality of education is 76, with a minimum score of 50 and a maximum score of 96, a standard deviation of 10.8, and a variance of 118.4, and it is categorized as good, with a frequency of 28 people, which is 53% . The conclusion of this article is that there is a significant influence of the leadership style of school principals on the quality of education in SMP Negeri 1 Berastagi.